Physiological signature of late-onset nonallergic asthma of obesity. Issue 3 (17th August 2020) - Dixon, Anne E.; Peters, Ubong; Walsh, Ryan; Daphtary, Nirav; MacLean, Erick S.; Hodgdon, Kevin; Kaminsky, David A.; Bates, Jason H.T.
Introduction: Obesity can lead to a late-onset nonallergic (LONA) form of asthma for reasons that are not understood. We sought to determine whether this form of asthma is characterised by any unique physiological features. Methods: Spirometry, body plethysmography, multiple breath nitrogen washout (MBNW) and methacholine challenge were performed in four subject groups: Lean Control (n=11), Lean Asthma (n=11), Obese Control (n=11) and LONA Obese Asthma (n=10). The MBNW data were fitted with a novel computational model that estimates functional residual capacity (FRC), dead space volume (VD ), the coefficient of variation of regional specific ventilation (CV, V′ E ) and a measure of structural asymmetry at the level of the acinus (sacin ). Results: Body mass index and waist circumference values were similar in both obese groups, and significantly greater than in lean asthmatic individuals and controls. Forced vital capacity was significantly lower in the LONA Asthma group compared with the other groups (p<0.001). Both asthma groups exhibited similar hyperresponsiveness to methacholine. FRC was reduced in the Obese LONA Asthma group as measured by MBNW, but not in obese controls, whereas FRC was reduced in both obese groups as measured by plethysmography. VD, CV, V′ E and sacin were not different between groups. Conclusions: Chronic lung compression characterises all obese subjects, as reflected by reduced plethysmographic FRC. Obese LONA asthma is characterised by a reduced ability to recruit closed lung units, as seen by reduced MBNW FRC, and an increased tendency for airway closure as seen by a reduced forced vital capacity. Obesity increases the risk of developing a late-onset nonallergic form of asthma. This form of obese asthma may be related to an increased tendency towards airway closure and inability to open the lungs with a deep breath. https://bit.ly/3eRdXv6